Pengaruh Spiritualitas Kristen, Efikasi dan keterampilan Literasi Informasi terhadap Integritas Akademik Mahasiswa Program Jarak Jauh - Dhama Gustiar Baskoro; Yonathan Winardi; Rambu Naha (SANCTUM DOMINE: JURNAL TEOLOGI, 2026)
The increasing prevalence of academic dishonesty in online learning and Gen-AI usage highlights the importance of examining the role of Christian spirituality, self-efficacy, and information literacy skills in strengthening academic integrity among distance education students. This study aimed to analyse the direct and moderating effects of Christian spirituality on students’ academic integrity using a quantitative approach with Partial Least Squares Structural Equation Modelling (PLS-SEM) involving 130 students from a Christian university in Indonesia. The outer model evaluation demonstrated that all constructs satisfied reliability and validity requirements (Composite Reliability >0.70; AVE >0.50). The inner model analysis revealed that Christian spirituality (β=0.274; t=3.687; p<0.001), self-efficacy (β=0.274; t=2.424; p=0.016), and information literacy (β=0.244; t=2.770; p=0.006) had significant positive effects on academic integrity, with the model explaining 41.1% of the variance (R²=0.411), indicating moderate explanatory power. However, Christian spirituality did not significantly moderate the relationships between self-efficacy or information literacy and academic integrity (p>0.05). The effect size analysis indicated that all direct effects were categorized as small (f²<0.15). Furthermore, the post-hoc power analysis showed that the sample size was adequate for detecting moderate to large effects but remained limited in detecting very small interaction effects. The study concludes that Christian spirituality functions as a foundational value directly supporting academic integrity; therefore, strengthening academic integrity among distance education students requires the simultaneous integration of faith-based education, self-efficacy development, and information literacy instruction.